SISTEM PAKAR DIAGNOSA PENYAKIT PADA GIGI BERBASIS WEB DENGAN PENALARAN FORWARD CHAINING - Muhammad Ifan Rifani Ihsan; Lady Agustine; Rizka Dahlia; Ahmad Fachrurozi (STEKOM PRESS, 2022)
Teeth are one of human‘s organs that feeds on food. As an organ, the tooth definitely can be attacked by some disease. There are many cases of dental disease that occur from dental diseases common to people to chronic dental diseases that can be dangerous. The low level of public concern about dental disease is a problem faced today. Evidenced by the small number of people who diligently consult with dentists about the health of their teeth. An alternative option is needed that can make it easier for people to be able to consult or diagnose dental health and disease without having to see a doctor of dental health. Therefore, in this essay an expert system was created to provide alternative choices for people. This expert system was created with the php hypertext preprocessor programming language. Using the forward chaining method as a tracking method. The purpose of making this expert system is to be able to be a substitute for a dental expert so that people can already do the diagnosis of dental disease anywhere and anytime.